PENGEMBANGAN AUGMENTED REALITY UNTUK APLIKASI PENGENALAN RUMAH ADAT NUSANTARA DENGAN METODE MDLC - Suartama, I Komang; Astawa, Ni Luh Putu Ning Septyarini Putri; Juliharta, I Gede Putu Krisna (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2024)
This research developed an educational media application based on Augmented Reality (AR) called "AR Rumah Adat Nusantara," aimed at introducing traditional houses of Indonesia to students. The primary issue addressed is the need to preserve local culture, which is increasingly being eroded by modernization. This application is expected to enhance students' understanding of Indonesia's cultural heritage. The development method used is the Multimedia Development Life Cycle (MDLC), and the study employs a mixed-method approach combining quantitative and qualitative data. Data collection techniques include interviews, observations, and literature review. The application was tested using black box testing to ensure all functions work as intended. The study participants consisted of educators and fourth-grade students from a non-formal educational institution in Gianyar Regency, Bali. The results indicate that the application was successfully developed with 100% functionality as confirmed through testing. The study concludes that AR technology has significant potential in enhancing the learning process, particularly in introducing and preserving local culture. The "AR Rumah Adat Nusantara" application is expected to be an effective and engaging learning tool, helping students to learn about and appreciate Indonesia's rich cultural heritage.